Factor XII Structure–Function Relationships - Shamanaev, Aleksandr; Litvak, Maxim; Ivanov, Ivan; Srivastava, Priyanka; Sun, Mao-Fu; Dickeson, S. Kent; Kumar, Sunil; He, Tracey Z.; Gailani, David (Seminars in Thrombosis and Hemostasis, 2023)
Factor XII (FXII), the zymogen of the protease FXIIa, contributes to pathologic processes such as bradykinin-dependent angioedema and thrombosis through its capacity to convert the homologs prekallikrein and factor XI to the proteases plasma kallikrein and factor XIa. FXII activation and FXIIa activity are enhanced when the protein binds to a surface. Here, we review recent work on the structure and enzymology of FXII with an emphasis on how they relate to pathology. FXII is a homolog of pro-hepatocyte growth factor activator (pro-HGFA). We prepared a panel of FXII molecules in which individual domains were replaced with corresponding pro-HGFA domains and tested them in FXII activation and activity assays. When in fluid phase (not surface bound), FXII and prekallikrein undergo reciprocal activation. The FXII heavy chain restricts reciprocal activation, setting limits on the rate of this process. Pro-HGFA replacements for the FXII fibronectin type 2 or kringle domains markedly accelerate reciprocal activation, indicating disruption of the normal regulatory function of the heavy chain. Surface binding also enhances FXII activation and activity. This effect is lost if the FXII first epidermal growth factor (EGF1) domain is replaced with pro-HGFA EGF1. These results suggest that FXII circulates in blood in a “closed” form that is resistant to activation. Intramolecular interactions involving the fibronectin type 2 and kringle domains maintain the closed form. FXII binding to a surface through the EGF1 domain disrupts these interactions, resulting in an open conformation that facilitates FXII activation. These observations have implications for understanding FXII contributions to diseases such as hereditary angioedema and surface-triggered thrombosis, and for developing treatments for thrombo-inflammatory disorders.
Keywords: factor XII; prekallikrein; factor XI; pro-HGFA; contact activation; kallikrein-kinin system